Penerapan Nilai Dzikir Dalam Layanan Bimbingan dan Konseling Pada siswa Bina Insani - Yunus Shofi; Muhammad Rizan Setiawan; Alif Nur Azis (Kampus Akademik Publiser, 2026)
This study explores the implementation of dhikr values within Guidance and Counseling (BK) services as a transformative solution to address social interaction issues and student indiscipline at SMA Bina Insani. Utilizing a descriptive qualitative approach, data were gathered through direct observation, in-depth interviews, and documentation with four students and one Guidance and Counseling teacher selected via purposive sampling. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings reveal that student infractions, such as truancy and escaping school activities, are primarily triggered by academic burnout and peer pressure from toxic circles. The integration of dhikr and weekly mujahadah serves as an effective religious psychotherapy instrument within Islamic Guidance and Counseling (BKI). This spiritual approach successfully induces emotional stabilization and inner peace, thereby reducing psychological resistance and making students more cooperative during counseling sessions. Consequently, behavioral changes occur through intrinsic motivation and internal awareness rather than fear of sanctions. Furthermore, this integration shifts the students' paradigm regarding BK teachers—from intimidating